PERBAIKAN SISTEM PEMUNGUTAN LAK DALAM RANGKA PENINGKATAN PRODUKSI - Ishak Sumantri (Pusat Penelitian dan Pengembangan Hasil Hutan, 1992)
A research on the improvement of lac harvesting system had been conducted in Probolinggo Forest Districts. Unit II Perum Perhutani, East Java. Harvesting system and plantation site were observed to find higher lac production.The result are as follows : – The selective system is better than total cut system in producing lac.–The plantation on top of the hill produce more lac than other places due to the richness of sun shine.